Prodigiosin induces apoptosis and inhibits autophagy via the extracellular signal-regulated kinase pathway in K562 cells. (October 2019) - Ji, Shuangbin; Sun, Rongli; Xu, Kai; Man, Zhaodi; Ji, Jiahui; Pu, Yunqiu; Yin, Lihong; Zhang, Juan; Pu, Yuepu
Abstract: Prodigiosin contains a tripyrrole skeleton and shows impressive anticancer potential in multiple cell lines. Numerous studies have been conducted on prodigiosin-induced apoptosis and the related mechanisms. However, few reports have considered the effects of prodigiosin on autophagy and the relationship between apoptosis and autophagy. Here, we examined whether prodigiosin affected apoptosis and autophagy through the extracellular signal-regulated (ERK) signaling pathway in K562 cells, employing cell proliferation, flow cytometry, caspase activity, and western blot analyses. Inhibition of the ERK signaling pathway with PD184352 was conducted to verify the role of this pathway on prodigiosin-mediated processes. Our findings revealed that prodigiosin inhibited the proliferation of K562 cells, increased reactive oxygen species (ROS), induced apoptosis and inhibited autophagy in K562 cells. Additionally, the ROS scavenger, N-Acetyl-L-cysteine (NAC), partially prevented prodigiosin-induced apoptosis but did not reduce prodigiosin-inhibited autophagy in K562 cells. Furthermore, prodigiosin treatment in K562 cells reduced the phosphorylation of c-Jun N-terminal kinases (JNKs) and P38, and activated ERK signaling pathway. When ERK1/2 phosphorylation was blocked by PD184352, prodigiosin-induced apoptosis and the inhibition of autophagy decreased significantly. Taken together, these results demonstrated that the ERK signaling pathway was involved in prodigiosin-induced apoptosis and prodigiosin-inhibited autophagy. Highlights: Prodigiosin induces apoptosis and inhibits autophagy at the same time. ROS is involved in prodigiosin-induced apoptosis but not autophagy. ERK signaling pathway is participated in prodigiosin-caused apoptosis and autophagy simultaneously.